Al-Taftāzānī’s Sources of Knowledge in Sharḥ al-Talwīḥ ‘alā al-Tawḍīḥ li Matn al-Tanqīḥ fī Uṣūl al-Fiqh - Ramli, Mohd Hilmi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2020)
This study discusses the sources of knowledge based on Sa‘d ‘Umar Mas‘ūd al-Taftāzānī’s (d. 492 A.H/ 1390 A.D) exposition in his uṣūl al-fiqh work Sharḥ al-Talwīḥ ‘alā al-Tawḍīḥ li Matn al-Tanqīḥ fī Uṣūl al-Fiqh. This study focuses on the active and dynamic inter-relational function of the senses (al-ḥiss) and the intellect (al-‘aql), which are the two key channels of knowledge established for the mukallaf, besides the true reports (khabar ṣādiq). Al-Taftāzānī expounds the nature of mukallaf’s external senses functioning to perceive sensible objects of knowledge, the function of the internal senses to perceive the intelligible object of knowledge, and the locuses of each of the internal senses are in the brain. Al-Taftāzānī asserts the prominence of the fifth internal sense, the Rational Imaginative (al-mufakkirah), above all the other internal senses. The function of the Rational Imaginative is not for reproduction only, but it also performs in creating (ibtikār) new form, which the form has not been imagined by the senses before it. In other words, it points to the potentiality of the soul of the mukallaf, to create new knowledge. Al-Taftāzānī discusses the four stages of the intellect, which he indicates that for the mukallaf, it is at least to acquire at the second level of the intellect; al-‘aql bi al-malakah (intelligence in habitus; intellectus in habitu), because the intellect at this level has already acquired the necessary knowledge and the conceptual knowledge of the Sharī‘ah, that allow mukallaf to act accordingly. This study found that al-Taftāzānī’s exposition on the senses and the intellect as channels of knowledge are not only descriptive, but prescriptive. As a result, the students, researchers, and scholars in the science of uṣūl al-fiqh can analyse the mukallaf not as a passive recipient of the legal judgment, but mukallaf is also the active interpreter of God’s legal judgment. It can therefore be concluded that al-Taftāzānī’s exposition contributed significantly to the deeper understanding of the epistemological and psychological aspects of mukallaf, as one of the key pillars in the science uṣūl al-fiqh.